Slit2N/Robo1 inhibit HIV-gp120-induced migration and podosome formation in immature dendritic cells by sequestering LSP1 and WASp. - Anil Prasad; Paula M Kuzontkoski; Ashutosh Shrivastava; Weiquan Zhu; Dean Y Li; Jerome E Groopman (PLoS ONE, 2012)
Cell-mediated transmission and dissemination of sexually-acquired human immunodeficiency virus 1 (HIV-1) in the host involves the migration of immature dendritic cells (iDCs). iDCs migrate in response to the HIV-1 envelope protein, gp120, and inhibiting such migration may limit the mucosal transmission of HIV-1. In this study, we elucidated the mechanism of HIV-1-gp120-induced transendothelial migration of iDCs. We found that gp120 enhanced the binding of Wiskott-Aldrich Syndrome protein (WASp) and the Actin-Related Protein 2/3 (Arp2/3) complex with β-actin, an interaction essential for the proper formation of podosomes, specialized adhesion structures required for the migration of iDCs through different tissues. We further identified Leukocyte-Specific Protein 1 (LSP1) as a novel component of the WASp-Arp2/3-β-actin complex. Pretreating iDCs with an active fragment of the secretory glycoprotein Slit2 (Slit2N) inhibited HIV-1-gp120-mediated migration and podosome formation, by inducing the cognate receptor Roundabout 1 (Robo1) to bind to and sequester WASp and LSP1 from β-actin. Slit2N treatment also inhibited Src signaling and the activation of several downstream molecules, including Rac1, Pyk2, paxillin, and CDC42, a major regulator of podosome formation. Taken together, our results support a novel mechanism by which Slit2/Robo1 may inhibit the HIV-1-gp120-induced migration of iDCs, thereby restricting dissemination of HIV-1 from mucosal surfaces in the host.